Parenting in poor environments : stress, support, and coping - Ghate, Deborah (Jessica Kingsley Publishers, 2002)
With a unique focus on the effects of poverty on parenting in Britain, this book explores what professionals and policy makers can do to support families living in poverty. The authors examine community-level poverty and its relationship to family and individual problems such as low income, poor mental health and child behavioural difficulties. Using data from the first nationally representative survey of parents living in especially poor circumstances, they assess the wider help parents receive, both through formal support services and through informal networks of family and friends. Drawing.